(The Effect of Using Cooperative Teaching Strategy in Improving Reading Skills for the Secondary School Students in the Sudan - Elrasool, Ahmed (Gezira Journal of Educational Sciences and Humanities; مجلد 13 عدد 2 (2016), 2018)
Abstract      The study aimed to identify the effect of using cooperative learning strategy on students learning of reading skill, the sample of the study consisted of (200) students from the Sudanese secondary schools in Al-Duiem locality who were divided into experimental group and control group. The researcher used pre and post test to collect the data, where the results of the study showed that using cooperative learning stimulate students to learn and help them achieve their goals., The results of the study showed that the cooperative learning develops the social skills of the students